Conductive carbon paste for automobile rearview mirror and preparation method of conductive carbon paste

By using chlorine acetic acid resin and polyurethane resin in the conductive carbon slurry, combined with conductive carbon powder, conductive graphite and other materials, the shortcomings of existing conductive carbon slurry in terms of weather resistance, chemical resistance and bonding strength are solved, and a high-performance conductive carbon slurry suitable for automotive rearview mirrors have been prepared.

CN119889770APending Publication Date: 2025-04-25SHANGHAI BAOYIN ELECTRONICS MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979142.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing conductive carbon slurry has shortcomings in weather resistance, chemical resistance and bonding strength, and it is difficult to meet the needs of components such as automotive rearview mirrors that have been exposed to complex environments for a long time.

Method used

By using a combination of chlorine acetic acid resin and polyurethane resin in the conductive carbon slurry, combined with conductive carbon powder, conductive graphite, organic solvents, plasticizers and other additives, a high-performance conductive carbon slurry for automotive rearview mirrors was prepared.

Benefits of technology

It significantly improves the weather resistance, chemical resistance and bonding strength of the conductive carbon slurry, maintains good processing performance, and is suitable for components in complex environments such as automotive rearview mirrors.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to conductive carbon paste for an automobile rearview mirror and a preparation method of the conductive carbon paste. The conductive carbon paste for the automobile rearview mirror comprises the following raw materials in percentage by weight: 40-60% of conductive carbon powder; 5-10% of conductive graphite; 10-20% of vinyl chloride-vinyl acetate resin; 5 to 15% of polyurethane resin; 10-25% of an organic solvent; 0-5% of a plasticizer; and 0-3% of other auxiliary agents. Compared with the prior art, the weather resistance, the chemical resistance and the bonding strength of the conductive carbon paste are remarkably improved, so that the conductive carbon paste is more suitable for parts, such as automobile rearview mirrors, which are exposed in a complex environment for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive carbon paste, and in particular to a conductive carbon paste for an automobile rearview mirror and a preparation method thereof. Background Art

[0002] With the development of automobile electronics and intelligence, the functions of automobile rearview mirrors are no longer limited to simple reflection and field of vision expansion, but integrate advanced functions such as heating and defrosting, automatic anti-glare, blind spot monitoring, etc. The realization of these functions is inseparable from high-performance conductive materials. As a key material in the manufacture of automobile rearview mirrors, the performance of conductive carbon paste directly affects the conductivity, durability and reliability of rearview mirrors.

[0003] At present, the commonly used conductive carbon paste in the market is mainly based on polyurethane resin. Although it has certain conductivity and processing properties, it still needs to be improved in terms of weather resistance, chemical resistance and bonding strength. Especially for parts such as car rearview mirrors that are exposed to complex environments for a long time, the performance of existing conductive carbon pastes often cannot meet the needs of long-term use. Summary of the invention

[0004] The purpose of the present invention is to provide a conductive carbon paste for automobile rearview mirror and a preparation method thereof, so as to improve the weather resistance, chemical resistance and bonding strength of the conductive carbon paste.

[0005] The object of the present invention can be achieved by the following technical solution: A conductive carbon slurry for a rearview mirror of an automobile, wherein the raw materials comprise the following components by weight percentage:

[0006] Conductive carbon powder: 40-60%;

[0007] Conductive graphite: 5-10%;

[0008] Chlorovinyl resin: 10-20%;

[0009] Polyurethane resin: 5-15%;

[0010] Organic solvent: 10-25%;

[0011] Plasticizer: 0-5%;

[0012] Other additives: 0-3%.

[0013] The invention can significantly improve the weather resistance, chemical resistance and bonding strength of the carbon paste by using the chlorovinyl resin and the polyurethane resin in combination, while maintaining good processing performance.

[0014] Preferably, the conductive carbon powder is a flake carbon powder with an average particle size of 1-5 microns. The flake carbon powder of the present invention can improve the conductive performance and filling density.

[0015] Further preferably, the conductive carbon powder has an average particle size of 2-4 microns, a bulk density of 0.5-1.4 g / ml, a tap density of 1.3-2.6 g / ml, and a specific surface area of ​​0.7-1.4 m 2 / g.

[0016] More preferably, the conductive carbon powder has a bulk density of 0.7-1.4 g / ml.

[0017] In the present invention, the conductive graphite can enhance the conductivity and improve the lubricity of the carbon paste.

[0018] Preferably, the conductive graphite is anisometric flaky graphite.

[0019] Further preferably, the conductive graphite is highly anisometric flaky graphite.

[0020] Further preferably, the conductive graphite has a particle size of 3-4 nm and a density of 0.1-0.14 g / cm 3 , with a specific surface area of ​​11-15m 2 / g highly anisometric flake graphite.

[0021] More preferably, the conductive graphite has a particle size of 3.5 nm and a density of 0.12 g / cm 3 , with a specific surface area of ​​13m 2 / g highly anisometric flake graphite.

[0022] Preferably, the chloroacetic acid resin is chloroacetic acid resin C17, purchased from Huntsman.

[0023] Preferably, the polyurethane resin is polyurethane resin K97, purchased from Huntsman.

[0024] In the present invention, the weather resistance, chemical resistance and bonding strength of the carbon paste can be significantly improved by using the chlorovinyl resin C17 and the polyurethane resin K97 in combination, while maintaining good processing performance.

[0025] Preferably, the organic solvent is one or more of dibasic acid ester, isophorone, and diethylene glycol ethyl ether. The organic solvent can dissolve the resin and adjust the viscosity.

[0026] Preferably, the plasticizer is one or more of hexylene glycol and dibutyl diglyceride.

[0027] Preferably, the other additives include one or more of a dispersant, a leveling agent, an anti-settling agent, and a defoaming agent.

[0028] A method for preparing the above-mentioned conductive carbon slurry for automobile rearview mirror comprises the following steps:

[0029] (1) Preparation of materials: weighing the raw materials according to the above components and weight percentages;

[0030] (2) Preparation of resin solution: Mix chloroacetic acid resin and polyurethane resin with an organic solvent at the same time, heat and maintain constant temperature until the resin is completely dissolved, and filter to remove impurities to obtain a resin solution;

[0031] (3) Preparation of conductive carbon slurry: Add conductive carbon powder, conductive graphite, plasticizer and other additives to the resin solution, mix them thoroughly in a mixer, and then disperse them at high speed to obtain a uniform slurry;

[0032] (4) Grinding and adjustment: The slurry is ground in a three-roll mill to a fineness of 5-15 μm, and the viscosity is adjusted to 18-25 Pa·S to obtain the conductive carbon slurry for the automotive rearview mirror.

[0033] Preferably, the heating temperature in the resin dissolving step is 60-72° C., and the constant temperature stirring time is 2-3 hours.

[0034] Preferably, the mixing in the conductive carbon slurry preparation step is performed using a planetary mixer or similar equipment at 450-550 rpm for 35-40 minutes.

[0035] Preferably, the high-speed dispersion is performed using a high-speed disperser at 2600-3000 rpm for 30-50 minutes.

[0036] More preferably, the high-speed dispersion is performed using a high-speed disperser at 2800 rpm for 40 minutes.

[0037] Preferably, the slurry is ground in a three-roll mill, the fineness of the carbon slurry is controlled within a certain range (5-15 microns) by roller fine-tuning, and the viscosity is adjusted to an appropriate value (such as 18-25 Pa·S), so that a high-performance conductive carbon slurry for automotive rearview mirrors is prepared.

[0038] The present invention provides a high-performance conductive carbon paste for automobile rearview mirrors and a preparation method thereof. The conductive carbon paste aims to solve the problems existing in the existing conductive carbon paste in terms of weather resistance, chemical resistance and bonding strength. The main raw materials include conductive carbon powder, conductive graphite, chlorovinyl resin, polyurethane resin, organic solvent, plasticizer and other additives. The high-performance conductive carbon paste is prepared through a specific ratio and preparation process.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The present invention provides a high-performance conductive carbon paste for automobile rearview mirrors and a preparation method thereof, which solves the problems existing in the existing conductive carbon paste in terms of weather resistance, chemical resistance and bonding strength.

[0041] 2. The present invention significantly improves the weather resistance, chemical resistance and bonding strength of the conductive carbon paste by introducing the combined use of two resins, making it more suitable for parts such as automotive rearview mirrors that are exposed to complex environments for a long time.

[0042] 3. The preferred characteristics of the conductive carbon powder and conductive graphite of the present invention and the coordinated use of the chloroacetic acid resin C17 and the polyurethane resin K97 significantly improve the conductivity, weather resistance, chemical resistance and bonding strength of the carbon paste.

[0043] 4. The present invention obtains a high-performance conductive carbon paste suitable for complex environments such as automobile rearview mirrors through raw material ratio and preparation method, which has excellent conductivity, weather resistance, chemical resistance and bonding strength.

[0044] 5. The preparation process of the conductive carbon paste of the present invention is simple and easy to control, and the raw material source is wide and the cost is low, which is conducive to industrial production.

[0045] 6. The conductive carbon paste prepared by the present invention has good conductivity, processing performance and printing performance, and can meet the high requirements of components such as automobile rearview mirrors for conductive materials.

[0046] 7. The conductive carbon paste of the present invention has good weather resistance. After testing simulating extreme climatic conditions, the conductive carbon paste of the present invention can maintain stable conductive properties and physical properties in a temperature range of -40°C to 85°C and in an environment with a relative humidity of less than 85%, and the weather resistance can reach a range of more than 72 hours in high and low temperature humidity tests.

[0047] 8. The conductive carbon paste of the present invention has good chemical resistance. When in contact with common hand sweat test liquid and other chemicals, the conductive carbon paste of the present invention exhibits extremely strong corrosion resistance. According to the industry test method, even under long-term contact, no obvious corrosion or performance degradation will occur.

[0048] 9. The conductive carbon paste of the present invention has good bonding strength, and the bonding strength on the PET substrate is extremely excellent. According to the adhesion test method, the bonding strength of the 3M tape test does not fall off, ensuring a firm adhesion on the PET substrate.

[0049] 10. Under normal temperature and pressure (25°C, relative humidity below 60%), the conductive carbon paste of the present invention can be used continuously for more than 50,000 hours with stable performance. In a harsh environment of high temperature and high humidity (such as 60°C, relative humidity 90%), its service life can also reach more than 20,000 hours.

[0050] 11. The conductive carbon paste of the present invention has good electrical conductivity, with a resistivity of 10 -2 ~10 -1 Ω·cm.

[0051] 12. The conductive carbon paste of the present invention is not only suitable for automobile rearview mirrors, but can also be widely used in other fields that require high-performance conductive materials, and has broad market prospects and application value. DETAILED DESCRIPTION

[0052] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0053] Example 1

[0054] Preparation:

[0055] Conductive carbon powder: Choose flake carbon powder with an average particle size of 2.5 microns, a loose density of 0.9g / ml, a tap density of 2.2g / ml, and a specific surface area of ​​1.1m 2 / g, accounting for 50% of the total weight.

[0056] Conductive graphite: highly isometric flake graphite with a particle size of 3.5nm and a density of 0.12g / cm 3 , with a specific surface area of ​​13m 2 / g, accounting for 7% of the total weight.

[0057] Chlorovinyl resin C17: 16% of the total weight.

[0058] Polyurethane resin K97: 10% of the total weight.

[0059] Organic solvent: divalent acid ester is selected, accounting for 15% of the total weight.

[0060] Plasticizer: Hexylene glycol was used, accounting for 1% of the total weight.

[0061] Additives: Add 0.5% dispersant and 0.5% leveling agent.

[0062] Preparation process:

[0063] Preparation of resin solution: Mix chloroacetic acid resin C17, polyurethane resin K97 and dibasic acid ester solvent, heat to 65°C and stir at constant temperature for 2.5 hours, ensure that the resin is completely dissolved and then filter.

[0064] Carbon slurry mixing: Add conductive carbon powder, conductive graphite, plasticizer and additives to the resin solution and mix at 450 rpm for 40 minutes using a planetary mixer.

[0065] High-speed dispersion: Use a high-speed disperser to disperse at 2800 rpm for 40 minutes to ensure that the slurry is uniform.

[0066] Grinding and adjustment: Grind in a three-roll mill to a fineness of about 7 microns and adjust the viscosity to 21 Pa·S.

[0067] Example 2

[0068] Preparation:

[0069] Conductive carbon powder: average particle size is 4 microns, bulk density is 1.2g / ml, tap density is 2.4g / ml, specific surface area is 1.3m 2 / g, accounting for 48% of the total weight.

[0070] Conductive graphite: 9% of the total weight.

[0071] Chlorovinyl resin C17: 14% of the total weight.

[0072] Polyurethane resin K97: 12% of the total weight.

[0073] Organic solvent: isophorone, accounting for 15% of the total weight.

[0074] Plasticizer: dibutyl diglyceride adipate, 1% by weight.

[0075] Additives: Add 1% dispersant.

[0076] Preparation process:

[0077] Resin dissolution: Mix the resin and isophorone, heat to 70°C, stir at constant temperature for 3 hours, and filter.

[0078] Mixing and dispersion: Add the conductive material, plasticizer and dispersant to the resin solution, use a high-speed mixer to mix at 550 rpm for 35 minutes, and then disperse at high speed until uniform.

[0079] Grinding: Grind in a three-roll mill to a fineness of about 6 microns.

[0080] Viscosity adjustment: Adjust the viscosity to 23 Pa·S.

[0081] Example 3

[0082] Preparation:

[0083] Conductive carbon powder: average particle size is 1.8 microns, bulk density is 0.7g / ml, tap density is 1.8g / ml, specific surface area is 0.9m 2 / g, accounting for 52% of the total weight.

[0084] Conductive graphite: 6% of the total weight.

[0085] Chlorovinyl resin C17: 13% of the total weight.

[0086] Polyurethane resin K97: 11% of the total weight.

[0087] Organic solvent: diethylene glycol ethyl ether, accounting for 17% of the total weight.

[0088] Plasticizer: Not used.

[0089] Additives: Add 0.5% leveling agent and 0.5% defoaming agent.

[0090] Preparation process:

[0091] Preparation of resin solution: Mix the resin with diethylene glycol ethyl ether, heat to 60°C, stir at constant temperature for 2 hours, and filter.

[0092] Mixing: Add conductive carbon powder, conductive graphite and additives into the resin solution and mix using a planetary mixer.

[0093] Dispersion and grinding: After high-speed dispersion, grind in a three-roll mill to a fineness of about 5 microns.

[0094] Viscosity and performance adjustment: Adjust the viscosity to 19Pa·S to ensure the stability of the slurry.

[0095] Example 4

[0096] Preparation:

[0097] Conductive carbon powder: average particle size is 3.5 microns, bulk density is 1.3g / ml, tap density is 2.5g / ml, specific surface area is 1.2m 2 / g, accounting for 45% of the total weight.

[0098] Conductive graphite: 10% of the total weight.

[0099] Chlorovinyl resin C17: 17% of the total weight.

[0100] Polyurethane resin K97: 9% of the total weight.

[0101] Organic solvent: dibasic acid ester and isophorone are mixed in a ratio of 2:1, accounting for 16.5% of the total weight.

[0102] Plasticizer: Hexanediol, 1% by weight.

[0103] Additives: Add 1% dispersant and 0.5% anti-settling agent.

[0104] Preparation process:

[0105] Resin dissolution: Heat the resin and mixed solvent to 68°C, stir at constant temperature for 2.5 hours, and filter.

[0106] Mixing and dispersing: Add conductive materials, plasticizers and additives, mix using a high-speed mixer, and disperse at high speed.

[0107] Grinding: Grind in a three-roll mill to a fineness of about 8 microns.

[0108] Performance optimization: Adjust the viscosity to 24Pa·S to ensure that the slurry is suitable for various coating processes.

[0109] Example 5

[0110] Preparation:

[0111] Conductive carbon powder: average particle size is 2 microns, bulk density is 0.8g / ml, tap density is 2.1g / ml, specific surface area is 1.0m 2 / g, accounting for 55% of the total weight.

[0112] Conductive graphite: 5% of the total weight.

[0113] Chlorovinyl resin C17: 12% of the total weight.

[0114] Polyurethane resin K97: 10% of the total weight.

[0115] Organic solvent: diethylene glycol ethyl ether and isophorone are mixed in a ratio of 1:1, accounting for 16% of the total weight.

[0116] Plasticizer: dibutyl diglyceride adipate, 1% by weight.

[0117] Additives: Add 0.5% leveling agent and 0.5% defoaming agent.

[0118] Preparation process:

[0119] Resin dissolution: Heat the resin and mixed solvent to 72°C, stir at constant temperature for 3 hours, and filter after ensuring complete dissolution.

[0120] Preparation of carbon slurry: Add conductive carbon powder, conductive graphite, plasticizer and additives into the resin solution and mix them using a planetary mixer.

[0121] Dispersion and grinding: After dispersion using a high-speed disperser, grind in a three-roll mill to a fineness of about 10 microns.

[0122] Viscosity and performance adjustment: Adjust the viscosity to 22Pa·S to ensure that the slurry has excellent electrical conductivity and processing performance.

[0123] The conductive carbon paste test results of the above five embodiments can be summarized as follows:

[0124] Embodiment 1:

[0125] Conductivity: Good performance, resistivity is as expected, suitable for applications requiring moderate conductivity.

[0126] Viscosity: moderate, easy to apply and process.

[0127] Stability: Maintain good stability during storage and use.

[0128] Weather resistance: After simulated aging tests, there is no significant decrease in performance.

[0129] Embodiment 2:

[0130] Conductive properties: Excellent, with a resistivity lower than that of Example 1, suitable for applications requiring high conductivity.

[0131] Viscosity: Slightly higher, but still within acceptable range and can be coated by adjusting process parameters.

[0132] Dispersion: The conductive material is evenly dispersed in the resin without obvious agglomeration.

[0133] Chemical resistance: Good resistance to common solvents and chemicals.

[0134] Embodiment 3:

[0135] Conductivity: above average, the resistivity is slightly higher than that of Example 2, but lower than that of Example 1.

[0136] Viscosity: Low, easy to apply, suitable for high-speed coating process.

[0137] Leveling: Excellent performance, the surface is smooth after coating without obvious defects.

[0138] Cost-effectiveness: The cost of raw materials is relatively low, with high cost-effectiveness.

[0139] Embodiment 4:

[0140] Conductive performance: stable, the resistivity is similar to that of Example 1, but the overall performance is better.

[0141] Viscosity: moderate to high. Coating performance can be optimized by adjusting the solvent ratio.

[0142] Weather and Chemical Resistance: After rigorous testing, it demonstrates excellent weather and chemical resistance.

[0143] Wide application range: suitable for a variety of coating processes and substrates.

[0144] Embodiment 5:

[0145] Electrical conductivity: Excellent, with a resistivity lower than all other embodiments, and the highest electrical conductivity among the five embodiments.

[0146] Viscosity: High, requires special coating process and equipment, but can be adjusted by adding diluent.

[0147] Processing performance: Although the viscosity is relatively high, good processing performance can be achieved after optimized process parameters.

[0148] Long-term stability: After long-term storage and use tests, the performance is stable without obvious degradation.

[0149] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A conductive carbon paste for automobile rearview mirror, characterized in that: The raw materials contain the following components by weight percentage: Conductive carbon powder: 40-60%; Conductive graphite: 5-10%; Chlorovinyl resin: 10-20%; Polyurethane resin: 5-15%; Organic solvent: 10-25%; Plasticizer: 0-5%; Other additives: 0-3%.

2. The conductive carbon paste for automobile rearview mirror according to claim 1, characterized in that: The conductive carbon powder is flaky carbon powder with an average particle size of 1-5 microns.

3. The conductive carbon paste for automobile rearview mirror according to claim 2, characterized in that: The conductive carbon powder has an average particle size of 2-4 microns, a bulk density of 0.5-1.4 g / ml, a tap density of 1.3-2.6 g / ml, and a specific surface area of ​​0.7-1.4 m 2 / g.

4. The conductive carbon paste for automobile rearview mirror according to claim 1, characterized in that: The conductive graphite is anisometric flaky graphite.

5. The conductive carbon paste for automobile rearview mirror according to claim 4, characterized in that: The conductive graphite has a particle size of 3-4 nm and a density of 0.1-0.14 g / cm 3 , with a specific surface area of ​​11-15m 2 / g highly anisometric flake graphite.

6. The conductive carbon paste for automobile rearview mirror according to claim 1, characterized in that: The organic solvent is one or more of dibasic acid ester, isophorone and diethylene glycol ethyl ether.

7. The conductive carbon paste for automobile rearview mirror according to claim 1, characterized in that: The plasticizer is one or more of hexylene glycol and dibutyl diglyceride.

8. The conductive carbon paste for automobile rearview mirror according to claim 1, characterized in that: The other additives include one or more of a dispersant, a leveling agent, an anti-settling agent, and a defoaming agent.

9. A method for preparing the conductive carbon paste for automobile rearview mirror according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of resin solution: Mix chloroacetic acid resin, polyurethane resin and organic solvent, heat and keep constant temperature until the resin is completely dissolved, and filter to obtain resin solution; Conductive carbon slurry preparation: Add conductive carbon powder, conductive graphite, plasticizer and other additives into the resin solution, mix and disperse to obtain a uniform slurry; Grinding and adjustment: Grinding the slurry in a three-roll mill to a fineness of 5-15 microns, adjusting the viscosity to 18-25 Pa·S, and obtaining the conductive carbon slurry for the automobile rearview mirror.

10. The method for preparing the conductive carbon paste for automobile rearview mirror according to claim 9, characterized in that: The heating temperature in the resin dissolution step is 60-72°C, and the constant temperature stirring time is 2-3 hours; The mixing in the conductive carbon slurry preparation step uses a planetary mixer at 450-550 rpm for 35-40 minutes, and the high-speed dispersion uses a high-speed disperser at 2600-3000 rpm for 30-50 minutes.